2011
DOI: 10.1002/tox.20706
|View full text |Cite
|
Sign up to set email alerts
|

Effects of malachite green on the mRNA expression of detoxification‐related genes in Nile tilapia (Oreochromis niloticus) and other major Chinese freshwater fishes

Abstract: The use of malachite green (MG) in fish farming is prohibited in China due to its potentially toxicological and carcinogenic nature, but it is still illegally used in some places. The aim of this study was to investigate the time and concentration-dependent responses of xenobiotic metabolizing and detoxification-related genes in diverse fishes exposed to MG both in vivo and in vitro. Experimental fish were administered to two exposure groups of malachite green (MG) (0.10 and 0.50 mg L⁻¹) for 8 h. The hepatocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 48 publications
(55 reference statements)
1
0
0
Order By: Relevance
“…The depressed CYP1A expression can be related to toxicant mediated inhibition of the gene activity [12]. Later, Dhamgaye et al [62] have reported MG as a substrate for CYP1A and credited the xenobiotic metabolism of MG into Leuco-MG (LMG) [63,64]. This LMG is accumulated in the tissues in conformity to present findings, illustrating the enhanced and prolonged MG toxicity.…”
Section: Discussionsupporting
confidence: 82%
“…The depressed CYP1A expression can be related to toxicant mediated inhibition of the gene activity [12]. Later, Dhamgaye et al [62] have reported MG as a substrate for CYP1A and credited the xenobiotic metabolism of MG into Leuco-MG (LMG) [63,64]. This LMG is accumulated in the tissues in conformity to present findings, illustrating the enhanced and prolonged MG toxicity.…”
Section: Discussionsupporting
confidence: 82%